A supramolecular network derived by rotaxane tethering three ureido pyrimidinone groups. Issue 36 (15th April 2019) - Rao, Si-Jia; Nakazono, Kazuko; Liang, Xiaobin; Nakajima, Ken; Takata, Toshikazu
Abstract : A rotaxane-cross-linked supramolecular network with good mechanical properties resulting from a trifunctional [2]rotaxane via intermolecular hydrogen bonding interactions. Abstract : A supramolecular network and its film were prepared via intermolecular hydrogen bonding of a [2]rotaxane with three ureido pyrimidinone groups. Adding less polar solvents such as CHCl3 to the rotaxane afforded a swollen rotaxane-cross-linked network. The properties of the film obtained by drying were evaluated to characterize it.